Effects of decentralisation on local public spending in Cameroon - Jean Raoul NKOUDOU BENGONO; Boniface Ngah EPO (المجلة الدولية للأداء الاقتصادي)
This study investigates the effects of fiscal decentralisation on local public spending in Cameroon, using a panel dataset of 213 municipalities over the period 2010–2020. The research aims to assess how the transfer of fiscal and administrative responsibilities from the central government to local authorities influences both operational and investment expenditures at the municipal level. Methodologically, the analysis employs ordinary least squares (OLS), fixed effects, and system GMM estimators to address endogeneity and unobserved heterogeneity, with local public spending (including both operating and investment outlays) as the dependent variable and fiscal decentralisation—measured as the share of municipal expenditures in total expenditures—as the key independent variable. Control variables include local revenues, urbanisation, central government subsidies, conflict incidence, and mayoral tenure.